The show must go on: an update on clinical experiences and clinical studies on novel pharmaceutical developments for the treatment of atopic dermatitis. Issue 4 (August 2020) - Honstein, Tatjana; Werfel, Thomas
Abstract : Purpose of review: This review reports on published clinical studies (full publications) with novel therapeutic agents on the treatment of atopic dermatitis with a focus on the last 2 years. Recent findings: Atopic dermatitis is a T-cell driven complex inflammatory skin disease. The secretion of cytokines involving not only particularly Th2 but also Th17 and Th22 cell subsets provides a broad spectrum of potential therapeutical targets. A couple of studies on atopic dermatitis with new therapeutical antibodies that target not only the Th2 cytokines IL-4, IL-13, IL- 31 but also additional targets, such as TSLP, IL-22 or IL-33, and innovative small molecules binding to the histamine-4 receptor, the phosphodiesterase-4, the aryl hydrocarbon receptor or downstream molecules like Janus kinases have recently been published with promising results on symptoms and signs of atopic dermatitis. Summary: Applications of newly developed drugs in clinical studies or already in daily practice show a substantial progress in the treatment of moderately to severely affected patients with atopic dermatitis not responsive to standard topical treatments with corticosteroids or topical calcineurin inhibitors alone. Moreover, novel treatment approaches generate new knowledge about (anti)inflammatory effects of immune modulations in atopic dermatitis and the heterogeneity of patient subgroups, which may stimulate further innovations in this field.